Infective endocarditis caused by Bartonella quintana in Greenland. Issue 3 (September 2014) - Jansen, Louise C.; Dargis, Rimtas; Bundgaard, Henning; Moser, Claus; Christensen, Jens Jørgen; Kemp, Michael
Abstract : Introduction: Bartonellosis has not been described previously in Greenland. Here, we present a case of infective endocarditis due to Bartonella quintana in a patient living in western Greenland. Case presentation: A 68‐year‐old man from Disko Island in western Greenland underwent aortic valve replacement because of infective endocarditis. Culture from blood and tissue was negative. PCR of bacterial DNA and DNA sequencing revealed DNA from B. quintana in the valve, and the finding was confirmed by species‐specific PCR. Conclusion: This case demonstrates the presence of B. quintana in Greenland. The finding emphasizes the importance of testing for unexpected agents when culture fails to identify the cause of a severe disease.